Analisys Impact Stock Split and Economic Value Added to Stock Return - Grima, Simon; Surtikanti, Surtikanti; Anggadini, Sri Dewi (International Business and Accounting Research Journal, 2020)
The purpose of this research is to analyse the impact before and after the stocks split on stock return, and analysing the impact of economic value added (EVA) to the stock return in the financial sector service company listed on the Indonesia Stock Exchange (IDX) period 2014-2019. The study method used event studies because the research is aimed at testing the information content of the market reaction of an announcement. The population of 250 financial statements of the company conducting a stock split is listed on the Indonesia Stock Exchange, using Purposif sample samples to 35 financial statements. Analyze data using different test and simple Linear regression. Researchers also tested whether there was a deviation of assumptions from test normality and autocorrelation. The results showed that there were no significant differences and negative value stock returns before and after the stock split. And there are significant and partial positive influences between the economic value added (EVA) on the stock return.